The Role of Shared Book Reading on Early Literacy: The Effects in terms of Home and School Environment - Figen Turan; Z. Güzin Topcu (Hacettepe University, 2018)
Shared book reading is a social activity in which an adult reads a book to a child or a group of children by expecting a different rate of participation from the child according to the type of reading. The literature supports that, during shared book reading process, children improve the abilities of receptive and expressive language; and depending on the technique of reading they improve the abilities of phonological awareness and print awareness. Important body of research shows that different practices of reading ((a) dialogic reading, (b) shared book reading, (c) interactive shared book reading, (d) print referencing) are used for the field of early intervention. As the most useful techniques among the early intervention techniques in which book-sharing was used, are interactive shared book reading and dialogic reading, which gave the child the most active role. There are some variables that affect the output during shared book reading. Depending on that fact, the attitudes and behaviours of the adults; the number of the children in the interaction; home and school context; following the interest of the children and expanding their answers; asking open-ended questions and children's active participation to the reading process are the factors that affect the shared book reading interaction. Some researchers claim that gender of the parent is another variable in this interaction. This research examines the different practices of shared book reading, the benefits of these specific practices and the variables which are considered as effective in shared book reading interaction.